Homogenization coarse graining (HCG) of the lattice discrete particle model (LDPM) for the analysis of reinforced concrete structures. (15th June 2018) - Lale, Erol; Rezakhani, Roozbeh; Alnaggar, Mohammed; Cusatis, Gianluca
Highlights: A homogenization coarse graining scheme is formulated to simulate concrete. The adopted fine scale model is the Lattice Discrete Particle Model (LDPM). Efficiency and accuracy of the method is verified by simulating several examples. Abstract: In this study, a coarse-graining framework for discrete, fine-scale models is formulated on the basis of multiscale homogenization. The model considered in this paper is the Lattice Discrete Particle Model (LDPM), which simulates concrete at the level of coarse aggregate pieces. In LDPM, the size of the aggregate particles follows the actual particle size distribution. Consequently, modeling large structural systems entirely with LDPM leads to a significant number of degrees of freedom and is not feasible with the currently available computational resources. To overcome this limitation, this paper proposes the formulation of a coarse-grained model obtained by (1) increasing the actual size of the particles in the finescale model by a specific coarsening factor and (2) calibrating the parameters of the coarse grained model by best fitting the macroscopic, average response of the coarse grained model to the corresponding fine scale one for different loading conditions. A Representative Volume Element (RVE) of LDPM is employed to obtain the macroscopic response of the fine scale and coarse grained models through a homogenization procedure. Accuracy and computational efficiency of the developed coarse graining method are verified by comparing the response of fine scale and coarse grained simulations of several reinforced concrete structural systems.